Benralizumab use in chronic eosinophilic pneumonia with eosinophilic bronchiolitis and chronic airway infection. Issue 8 (20th July 2021) - Takano, Tomotsugu; Inutsuka, Yuh; Nakamura, Satoshi; Ando, Nobuhisa; Komori, Masashi
Abstract: Chronic eosinophilic pneumonia (CEP) is a rare disorder characterized by marked accumulation of eosinophils in lung tissues and/or bronchoalveolar lavage fluid (BALF). Patients with CEP usually respond well to corticosteroids. However, more than half of these patients relapse while tapering and/or after discontinuing corticosteroids. Long‐term adverse effects of corticosteroids can be serious. We report a case of comorbid CEP, severe bronchial asthma, eosinophilic bronchiolitis, and chronic airway infection. Corticosteroid treatment induced remission of the CEP, but recurrent exacerbation of the chronic airway infection occurred. Thus, she was treated with benralizumab, a monoclonal antibody against the alpha‐chain of interleukin‐5 receptor. After the initiation of benralizumab, the steroid was stopped successfully and her CEP, asthma, and airway infection remained well controlled. Micronodular nodules on high‐resolution computed tomography (HRCT) reflecting bronchiolitis were also improved with benralizumab treatment. Benralizumab may be a treatment option for patients not tolerating steroids. Abstract : Chronic eosinophilic pneumonia (CEP) is an idiopathic disorder characterized by an abnormal accumulation of eosinophils in the interstitium and alveolar spaces of the lungs. The standard treatment for CEP is the administration of corticosteroids, but drug‐related complications occur often. Here, we report a case of successful benralizumab treatment for comorbid CEP, severe bronchial asthma, and chronic airway infection.